Meta Analisis Pengaruh Digitalisasi Terhadap Peningkatan Dan Perkembangan UMKM Di Kota Tangerang Selatan - Aisha, Neila (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2025)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in the nation's economic development, especially in encouraging economic growth and development. This research examines several journals regarding the influence of digitalization on the improvement and development of MSMEs in South Tangerang City. In the context of the rapid growth of digital technology, MSMEs face the challenge of expanding their market reach and increasing their sales. The use of digital platforms is an important solution in achieving this goal. This research aims to provide an in-depth understanding of how MSMEs can optimize digital platforms to increase visibility, develop brands and increase sales. Through a literature review, this research identifies the importance of digitalization, the benefits of integrating knowledge sources through digital platforms, and the positive impact of digital marketing on consumer purchasing interest and MSME income. The use of digitalization has been proven to increase income and development of MSMEs in any city. The South Tangerang City Government, through the Department of Cooperatives and UMKM, said that 60% of MSMEs in South Tangerang City have not used digitalization, while 30% of MSMEs have used digitalization. Therefore, regional or central governments need to support by holding digitalization training for MSMEs